De Novo Amino Acid Biosynthesis in Potato Tubers Is Regulated by Sucrose Levels - Roessner-Tunali, Ute (The American Society for Plant Biologists, 2003)
Plant growth and development are strongly dependent on sink-source interactions. In the majority of plants, sucrose (Suc) is the dominant form in which photo-assimilate is transported from source to sinks. Although the effects of Suc on photosynthetic metabolism have been intensively studied, the effect of Suc supply on metabolism in sink organs has received relatively little attention. For this reason, we performed a detailed characterization of the metabolism of potato (Solanum tuberosum) plants in which the Suc supply to the tuber was restricted by genetic or environmental perturbation. These characterizations revealed a clear inverse relationship between the levels of Suc and free amino acids. When data obtained from this study were considered alongside our previous work, a negative correlation between tuber Suc and amino acid content became apparent. Analysis of the transcript levels of key enzymes involved in amino acid biosynthesis revealed that several of these were increased under these conditions. Taken together, these data strongly suggest that Suc regulates amino acid biosynthesis in storage tissues such as potato tubers, most probably at the level of transcription.